La recuperación de cartera y su incidencia en el capital de trabajo de la "Cooperativa de Radio Taxi Machala". - Andrades Romero, Tania Mariuxi (My University, 2019)
The past due portfolio corresponds to a complicated topic in its granting and subsequent monitoring, its origin is formed by the different economic activities that a company registers in the accounting processes in a fiscal period; In this circumstance, the aforementioned subject must be analyzed in detail in order to give an understanding to the senior management of the organization; also, financial indicators of working capital, current ratio, average accounts receivable, equity debt ratio were applied, which allowed evaluating the results of the economic situation of the company, making a comparison with previous years; for making decisions based on its assets. In addition, confidence levels were used to measure delinquency, accounts receivable, portfolio recovery, in percentage terms, differentiating accounts from financial reports, which allowed a diagnosis of the company's financial weaknesses to be obtained. Also, the comparison of the most important accounts of the asset was applied, which allowed us to know the negative impact that the company has on the other accounts of the financial statements. In addition, it is necessary to describe that the bibliographic and field methodologies were used to obtain the information, since the criteria of scientific articles regarding the accounting field were considered, in order to demonstrate in practice the consistent results. In order to meet the stated objectives, the processes of granting loans were evidenced, which allowed us to verify its limits and compared with its economic performance of the entity. Likewise, the main objective is to analyze the incidence in working capital in relation to the recovery of the portfolio in the years 2017 to 2018, using the research methods, the general and specific objectives were established, corroborating the data through the interview . The deductions obtained reliably indicated that not using internal procedures to collect the overdue portfolio directly influenced the working capital, as a result, the company does not have enough liquidity to cover the daily needs. The research is based on the annual analysis of delinquency levels, the measurement of working capital, and the calculation of accounts receivable, thereby determining the weak points in the financial statements. By using these levels that allow an improvement production, this allows the correct participation of the partners and senior managers of the company under study. When examining an organization that allows for profitability growth within a society, new companies are encouraged to make the necessary changes in the credit allocation processes; what will allow to increase the capital of work with this allow to satisfy the needs. The profitability that a company has is the fundamental pillar on which the stability of the entity is expressed, and this is achieved thanks to an efficient administration and accounting process in which accounting strategies and policies are applied. Consequently, the resources used for the development of the organization will be optimized.
La cartera vencida corresponde a un tópico complicado en su otorgamiento y posterior seguimiento, su origen se forma de las diferentes actividades económicas que una empresa registra en los procesos contables en un periodo fiscal; en tal circunstancia se debe analizar de manera minuciosa el tema referido con el fin de dar entendimiento a los altos mandos de la organización; también, se aplicaron indicadores financieros de capital de trabajo, razón corriente, cuentas por cobrar promedio, razón deuda patrimonio, los cuales permitieron evaluar los resultados de la situación económica de la empresa, haciendo una comparación con años anteriores; para la toma decisiones basados en la patrimonio de la misma. Además, se utilizó niveles de confianza para medir la morosidad, las cuentas por cobrar, la recuperación de cartera, en términos porcentuales, diferenciando las cuentas de los informes financieros, lo que permitió obtener un diagnóstico de las debilidades financieras de la empresa. También, se aplicó la comparación de las cuentas más importantes del activo, lo que permitió saber la afectación negativa que tiene la empresa en las demás cuentas de los estados financieros. Además, es menester describir que para obtener la información se utilizó las metodologías bibliográficas y de campo, por cuanto se consideraron los criterios de artículos científicos referentes al ámbito contable, con el fin de demostrar en la practicidad los resultados coherentes. Para cumplir con los objetivos planteados se evidenció los procesos del otorgamiento de créditos lo que permitió constatar sus límites y se comparó con su rendimiento económico de la entidad. Así mismo, el principal objetivo es analizar la incidencia en el capital de trabajo en relación a la recuperación de cartera en los años 2017 a 2018, utilizando los métodos de investigación se estableció los objetivos generales y específicos, corroborando los datos a través de la entrevista. Las deducciones obtenidas indicaron fehacientemente que no utilizar procedimientos internos para realizar el cobro de la cartera vencida influye directamente en el capital de trabajo, en consecuencia de ello la empresa no tiene la suficiente liquidez para cubrir las necesidades cotidianas. La investigación se fundamenta en el análisis anual de los niveles de morosidad, la medición del capital de trabajo, y el cálculo de las cuentas por cobrar, logrando con esto determinar los puntos débiles en los estados financieros. Al utilizar estos niveles que permiten una producción de mejora, esto permite una participación correcta de los socios y altos mandos de la empresa objeto de estudio. Al examinar una organización que permite el crecimiento de rentabilidad dentro de una sociedad, se motiva a nuevas empresas, a realizar los cambios necesarios en los procesos de asignación de créditos; lo que permitirá aumentar el capital de trabajo con ello permita satisfacer las necesidades. La rentabilidad que una empresa posee, es el pilar fundamental sobre el cual se plasma la estabilidad de la entidad, y esto se logra gracias a un proceso de administración y contabilidad eficiente en el cual se apliquen estrategias y políticas contables. En consecuencia de aquello se va a optimizar los recursos utilizados para el desarrollo de la organización.
Keywords: CARTERA VENCIDA; MOROSIDAD; CUENTAS POR COBRAR; CAPITAL DE TRABAJO